2013
DOI: 10.1016/j.soard.2013.03.016
|View full text |Cite
|
Sign up to set email alerts
|

Predictors and outcomes of adolescent bariatric support group attendance

Abstract: Background Attending support groups connects adults undergoing bariatric surgery to peers and may improve weight loss efficacy. Predictors and outcomes of support group attendance of adolescents undergoing bariatric surgery are unknown. Objective The objective of this cohort study was to determine the rate, predictors, and outcomes of support group attendance in a free-standing adolescent bariatric program. Setting Academic children’s hospital in the U.S. Methods Charts of 68 consecutive adolescents who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…Adherence behaviors are important to the overall clinical management of individuals receiving bariatric surgery, as missing routine appointments results in suboptimal care, and failure to follow guidelines for diet or vitamin supplementation affects weight loss (6) and risk for malnutrition (9, 10) . However, extant research on bariatric surgery (4, 6, 8, 1116) includes a range of different adherence behaviors (e.g., attendance at postoperative appointments or support groups, following recommendations for diet and physical activity or multivitamin therapy), which limits comparisons across studies. Additional research is needed to better understand modifiable factors affecting adherence.…”
Section: Introductionmentioning
confidence: 99%
“…Adherence behaviors are important to the overall clinical management of individuals receiving bariatric surgery, as missing routine appointments results in suboptimal care, and failure to follow guidelines for diet or vitamin supplementation affects weight loss (6) and risk for malnutrition (9, 10) . However, extant research on bariatric surgery (4, 6, 8, 1116) includes a range of different adherence behaviors (e.g., attendance at postoperative appointments or support groups, following recommendations for diet and physical activity or multivitamin therapy), which limits comparisons across studies. Additional research is needed to better understand modifiable factors affecting adherence.…”
Section: Introductionmentioning
confidence: 99%
“…The risks and benefits of caregiver bariatric surgery on adolescent patient bariatric surgery outcomes are unknown, although this is an anticipated area of investigation within the Teen-LABS consortium and associated ancillaries [30]. While the present findings do not indicate that caregiver(s) history of bariatric surgery contributes to adolescents reaching or withdrawing from surgery, there is some evidence to suggest that it can contribute to less engagement in postoperative program opportunities [31] and should be a continued area of study.…”
Section: Discussionmentioning
confidence: 73%
“…A total of 36 studies were found that met the search criteria. The majority of studies were reviews ( n = 16, Table ), 8 were observational, 7 were case‐control studies, 3 were quasi‐experimental/case‐control studies, and 2 were RCTs (1 was a methods paper only) (Table ). No studies that tested the combination of pharmacotherapy interventions with MBS were found.…”
Section: Resultsmentioning
confidence: 99%
“…The search revealed seven longitudinal cohort design studies that included some combination of lifestyle interventions and MBS. None of the studies included pharmacotherapy support for MBS.…”
Section: Resultsmentioning
confidence: 99%